hiPSC-derived cardiac fibroblasts dynamically enhance the mechanical function of hiPSC-derived cardiomyocytes on an engineered substrate - Mitchell Josvai; Mitchell Josvai; Jodi Lawson; Jodi Lawson; Harshal Kanade; Harshal Kanade; Meghana Kalluri; Meghana Kalluri; Corey L. Anderson; Jianhua Zhang; Alana Stempien; Alana Stempien; et al. (Frontiers in Bioengineering and Biotechnology)
IntroductionCardiac fibroblasts deposit and turnover the extracellular matrix in the heart, as well as secrete soluble factors that play critical roles in development, homeostasis, and disease. Coculture of CFs and human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes (CMs) enhances CM mechanical output, yet the mechanism remains unclear.MethodsHere, we use an in vitro engineered platform to compare the effects on CM mechanical function of direct CM-CF Coculture and soluble signaling alone through CF Conditioned Medium to a CM Only monoculture. Mechanical analysis is performed using digital image correlation and custom software to quantify the coordination and organization of CM contractile behavior.ResultsCM-CF Coculture induces larger CM contractile strains, and an increased rate of spontaneous contraction compared to CM Only. Additionally, CM-CF Cocultures have increased contractile anisotropy and myofibril alignment and faster kinetics. The paracrine effects of fibroblast conditioned medium (FCM) are sufficient to induce larger contractile strains and faster contraction kinetics with these effects remaining after the removal of FCM. However, FCM does not influence CM spontaneous rate, contractile alignment, anisotropy, or relaxation kinetics compared to CM Only control.DiscussionThese data suggest that hiPSC-CFs exert dynamic and multifactorial effects on the mechanical function of hiPSC-CMs and highlight the importance of CFs in both the native heart and in vitro cardiac models. Further, this work demonstrates the applicability of the coculture–conditioned medium–monoculture paradigm to decouple the effects of paracrine factor and cell-cell signaling on hiPSC-CM mechanical function and maturation.